The Dimensionality of Signs, Tools, and Models : An Introduction - Bunn, James H., 1938- (Book collections on Project MUSE., 1981)
The present study introduces the ways that any instrument works according to its dimensional limits. I have followed. Uncle Toby's hobby horse and have divided the chapters so they correspond with the several Euclidean dimensions. The first chapter concerns three-dimensional signs, tools, and models as they exist 'in the round'; the second chapter explores two-dimensional pictographs such as maps and graphs; the third chapter outlines some basics of one-dimensional signs that work in time; and the fourth chapter explores models that are apparently 'whole systems'.